1998
DOI: 10.1093/emboj/17.19.5776
|View full text |Cite
|
Sign up to set email alerts
|

sigma R, an RNA polymerase sigma factor that modulates expression of the thioredoxin system in response to oxidative stress in Streptomyces coelicolor A3(2)

Abstract: We have identified an RNA polymerase sigma factor, sigmaR, that is part of a system that senses and responds to thiol oxidation in the Gram-positive, antibiotic-producing bacterium Streptomyces coelicolor A3(2). Deletion of the gene (sigR) encoding sigmaR caused sensitivity to the thiol-specific oxidant diamide and to the redox cycling compounds menadione and plumbagin. This correlated with reduced levels of disulfide reductase activity and an inability to induce this activity on exposure to diamide. The trxBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
229
2
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(239 citation statements)
references
References 40 publications
7
229
2
1
Order By: Relevance
“…The arrangement of genes at the M. tuberculosis sigH locus resembles that of the Streptomyces coelicolor A3(2) sigR locus (38,39), and it has been shown that the gene adjacent to sigR (rsrA) inhibits SigR activity by functioning as SigR-sequestering anti-factor (40). Because MT3318 transcriptional levels parallel those of sigH, it appears likely that the SigH and the MT3318 gene product are produced in equimolar quantities.…”
Section: Construction Of the Sigh Mutant And Complemented Strainmentioning
confidence: 99%
“…The arrangement of genes at the M. tuberculosis sigH locus resembles that of the Streptomyces coelicolor A3(2) sigR locus (38,39), and it has been shown that the gene adjacent to sigR (rsrA) inhibits SigR activity by functioning as SigR-sequestering anti-factor (40). Because MT3318 transcriptional levels parallel those of sigH, it appears likely that the SigH and the MT3318 gene product are produced in equimolar quantities.…”
Section: Construction Of the Sigh Mutant And Complemented Strainmentioning
confidence: 99%
“…Thioredoxin and thioredoxin reductase of M. tuberculosis have been shown to reduce peroxides and dinitrobenzenes with higher efficiency under anaerobic conditions (Zhang et al, 1999). In Streptomyces coelicolor the trxB operon has been found to be controlled by SigR (Paget et al, 1998) and its homologue in M. tuberculosis is designated SigH. Several studies have indicated that the sigma factors SigB, SigE, SigF and SigH in M. tuberculosis and M. smegmatis are involved in adaptation to several stresses, including heat shock and oxidative stress (Chen et al, 2000;Fernandes et al, 1999;Hu & Coates, 1999;Manganelli et al, 1999).…”
Section: Stress Proteinsmentioning
confidence: 99%
“…Further evidence for the distinction between peroxide stress and disulphide stress has emerged from analysis of the Streptomyces coelicolor s R regulon (Paget et al, 2001a). Induction of the s R regulon with diamide activates transcription of thioredoxin and thioredoxin reductase, thereby acting to restore oxidized thiols in the cell to their appropriate reduced state (Paget et al, 1998). The activity of s R is regulated by RsrA, the cognate antis factor (Kang et al, 1999), which is a zinc metalloprotein that binds s R to form an inactive complex.…”
Section: Introductionmentioning
confidence: 99%